A STUDY ON THE EFFECT OF CURING PERIOD ON THE STRENGTH OF CEMENT BRICK USING SAGO FINE WASTE AS CEMENT REPLACEMENT - Abd Wahabl, Norhayati; Adnanl, Suraya Hani; Ibrahim, Abdul Hadi Izaan; Mohamad, Mazizah Ezdiani; Osman, Mohamad Hairi; Jamellodin, Zalipah; Abdul Hamid, Noor Azlina (2023)
This study presents the effect of curing period towards properties of cement brick made up of cement, sand, and sago fine waste (SFW) as cement replacement. The percentage of replacement for SFW is in range between 0% to 10%. The strength of cement bricks was investigated based on curing period of 7, 28, 56, and 90 days and the density of the bricks were also recorded. Result shows the density of the brick decreases as the percentages of replacement of SFW increase. As per ASTM C55-11, bricks specimens for replacement 2 and 4% of SFW were categorized under normal brick category, while 6 to 10% as medium weight category. SFW has a substantial impact on the compressive strength of brick in which increasing the percentages of SFW lowers the brick's value of strength. The longer the curing process takes, the stronger the brick becomes. All bricks met the requirements of class 1, 2, and 3 load-bearing bricks, according to Malaysian standard MS 1933: Part 1: 2007 which shows the potential of SFW as a revolutionary pozzolanic material for more environmentally friendly bricks.